"Experiences of the burden of treatment"—Patient reports of facilitated subcutaneous immunoglobulin treatment in adults with immunodeficiency. Issue 23 (26th July 2018) - Petersson, Christina; Fust, Ramona; Hagstedt, Carina; Wågström, Per; Nilsdotter‐Augustinsson, Åsa
Abstract : Aims and objectives: To evaluate patient‐reported experiences of facilitated subcutaneous immunoglobulin treatment in adults with primary or secondary immunodeficiency. Background: Decreased levels of circulating antibodies (humoral immunodeficiency) are often associated with higher infection rates which cause problems in daily living, for example, symptoms of severe and recurrent bacterial infections that may cause chronic lung diseases. For some diagnoses, treatment with immunoglobulin becomes critical and lifelong. The acceptability of administration forms is important to achieve adherence to treatment and to increase quality of life for these patients. Design: Convergent mixed‐method approach. Methods: A structured telephone interview with nine questions evaluated on a score scale about treatment experience, satisfaction and ancillary supplies was used, followed by open‐ended questions for each item. Results: Prohibiting factors were revealed, exemplified by problems due to technical issues and ancillary supply issues. Promoting factors were shown by high a satisfaction according to the score‐scale when combining treatment with daily life as well as increased well‐being. Facilitated subcutaneous immunoglobulin treatment led to fewer treatment sessions, with a time‐saving aspect also described by high scores in the item concerning longer treatment interval. Conclusions: The opportunity to be given the best possible treatment plan adjusted for each patient's situation is central. Healthcare professionals should discuss the different aspects that can promote and inhibit the outcomes of treatment. Relevance to clinical practice: The results can help professionals to understand different factors that may impinge on the patients' everyday life when they are forced into a lifelong treatment regimen. This knowledge is also important for nurses who have a responsibility to promote health concerning patients with long‐term conditions in general.